2015
DOI: 10.1111/and.12453
|View full text |Cite
|
Sign up to set email alerts
|

Feeding hydroalcoholic extract powder ofLepidium meyenii(maca) increases serum testosterone concentration and enhances steroidogenic ability of Leydig cells in male rats

Abstract: Although Lepidium meyenii (maca), a plant growing in Peru's central Andes, has been traditionally used for enhancing fertility and reproductive performance in domestic animals and human beings, effects of maca on reproductive organs are still unclear. This study examined whether feeding the hydroalcoholic extract powder of maca for 6 weeks affects weight of the reproductive organs, serum concentrations of testosterone and luteinising hormone (LH), number and cytoplasmic area of immunohistochemically stained Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…Additionally, several clinical studies have demonstrated that maca increases the number and the motility of spermatozoa and increases sexual function in humans (Gonzales et al, , ; Lee, Lee, You, & Ha, ). In studies that were done with mammalian experimental models, maca administration was also found to improve sperm quality and spermatogenesis (Chung, Rubio, Gonzales, Gasco, & Gonzales, ; Gasco, Aguilar, & Gonzales, ; Gonzales et al, , ; Gonzales, Gonzales‐Castaneda, & Gasco, ; Gonzales, Rubio, Chung, Gasco, & Villegas, ; Sanchez‐Salazar & Gonzales, ; Yucra, Gasco, Rubio, Nieto, & Gonzales, ; Zhang, Zhou, & Ge, ) and the steroidogenic capacity of rat's Leydig cells (Ohta et al, ). Furthermore, the ejaculate volume, erection, mounting activity, sperm quality and the number of bulls that had undamaged plasma membrane acrosome after maca supplementation were increased after two spermatogenic cycles (Clement, Kneubühler, Urwyler, Witschi, & Kreuzer, ).…”
Section: Lepidium Meyeniimentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several clinical studies have demonstrated that maca increases the number and the motility of spermatozoa and increases sexual function in humans (Gonzales et al, , ; Lee, Lee, You, & Ha, ). In studies that were done with mammalian experimental models, maca administration was also found to improve sperm quality and spermatogenesis (Chung, Rubio, Gonzales, Gasco, & Gonzales, ; Gasco, Aguilar, & Gonzales, ; Gonzales et al, , ; Gonzales, Gonzales‐Castaneda, & Gasco, ; Gonzales, Rubio, Chung, Gasco, & Villegas, ; Sanchez‐Salazar & Gonzales, ; Yucra, Gasco, Rubio, Nieto, & Gonzales, ; Zhang, Zhou, & Ge, ) and the steroidogenic capacity of rat's Leydig cells (Ohta et al, ). Furthermore, the ejaculate volume, erection, mounting activity, sperm quality and the number of bulls that had undamaged plasma membrane acrosome after maca supplementation were increased after two spermatogenic cycles (Clement, Kneubühler, Urwyler, Witschi, & Kreuzer, ).…”
Section: Lepidium Meyeniimentioning
confidence: 99%
“…androgens, male infertility, medicinal plants, plant extracts, testis and the steroidogenic capacity of rat's Leydig cells (Ohta et al, 2016). Furthermore, the ejaculate volume, erection, mounting activity, sperm quality and the number of bulls that had undamaged plasma membrane acrosome after maca supplementation were increased after two spermatogenic cycles (Clement, Kneubühler, Urwyler, Witschi, & Kreuzer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, there are reports that administration of Maca enhances spermatogenesis, fertility and sexual behaviour; effects which are likely due to its phytosterols or phytoestrogens content (Wang, Wang, McNeil, & Harvey, 2007), and its androgen-like effects (Gonzales, Ruiz, Gonzales, Villegas, & Cordova, 2001;Zheng et al, 2000). There are studies that have reported that Maca has no effect on levels of hormones such as testosterone, follicle stimulating hormone, luteinising hormone or estrogens (Gonzales et al, 2009) in humans or rodents; however, a few other studies have reported that Maca increases serum testosterone levels and steroidogenic ability of leydig cells in rats (Ohta et al, 2016). There are studies that have reported that Maca has no effect on levels of hormones such as testosterone, follicle stimulating hormone, luteinising hormone or estrogens (Gonzales et al, 2009) in humans or rodents; however, a few other studies have reported that Maca increases serum testosterone levels and steroidogenic ability of leydig cells in rats (Ohta et al, 2016).…”
Section: Lepidium Meyenii (Maca) Is a Peruvian Hypocotyl Found In Cenmentioning
confidence: 99%
“…CYP was also associated with morphological evidence of tissue injury (testis and epididymis (Cicero, Bandieri, & Arletti, 2001;Zheng et al, 2000) and sperm count (Chung et al, 2005) following oral administration of various extracts of Maca hypocotyls. The ability of Maca to counteract CYP-induced changes in the male reproductive system has been related to its androgen-like effects (Gonzales et al, 2001;Zheng et al, 2000), and improved steroidogenic ability of Leydig cells (Ohta et al, 2016). The ability of Maca to counteract CYP-induced changes in the male reproductive system has been related to its androgen-like effects (Gonzales et al, 2001;Zheng et al, 2000), and improved steroidogenic ability of Leydig cells (Ohta et al, 2016).…”
Section: Effect Of Maca On Relative Morphometry Of the Testismentioning
confidence: 99%
“…Maca, a native plant in the central Andean region, possesses high carbohydrate, protein and unsaturated fatty acid contents (Cl ement et al, 2010). It was found to be effective for treating arthritis, preserving cognitive function in middle-aged mice, improving memory, regulating hormone secretion and enhancing fertility (Gonzales et al, 2006;Rubio et al, 2007;Efthimiou & Kukar, 2010;Uchiyama et al, 2014;Guo et al, 2016;Ohta et al, 2016). New areas for maca cultivation have been developed in other highaltitude regions including Yunnan province of China.…”
Section: Introductionmentioning
confidence: 99%